Storms and infant mortality in the Philippines - Orderud, Hilde (Elsevier, 2025)
Storms are one of the most frequent natural hazards and are expected to become more extreme as climate change proceeds. This paper investigates storms classified as disasters and infant mortality in the Philippines. Data from the Philippine Demographic and Health Surveys from 2003, 2008, and 2017 are combined with data on storms from the Emergency Events Database (EM-DAT) and the Geocoded Disasters Dataset. Storms included in EM-DAT are disasters with human and economic impact on the population. The lagged and immediate impact of storms are considered by including disasters occurring from five years prior to birth to two months after birth. The data are analysed with linear probability models and mother fixed-effects. The results show limited or no association between storms and infant mortality, which reflects a positive overall development in the Philippines over recent years. Improvements in disaster management systems are likely to have made communities and households more resilient.